Giving primacy to accountability in waqf accounting - Osman@Hussin, Ahmad Zamri; Hamdan, Norman (Centre for Islamic Economics (CIE) Kulliyyah of Economics and Management Sciences (KENMS) International Islamic University Malaysia (IIUM), 2016)
Objective – The objective of this paper is to argue for any institution established under waqf concept to give primacy on accountability over other consideration. The development of accounting standard is founded upon its conceptual framework. In waqf setting this foundation needs to be based on concepts suitable to the purpose of its being, i.e., waqf. Accountability is proposed to be the overarching concept for any new standard developed afterwards while other concepts is allowed as long as its pursuit does not contradict accountability concept. Methods - The paper reviews literatures on the objectives of information provision for accounting entity. It discusses two major lines of arguments in determining the overriding concept grounding the development of standards for a particular form of organisations or/and sectors. Findings – The purpose of information provision from accounting/reporting perspective should be congruent with the nature of the entity. Accountability is argued to embody the spirit of waqf better than to decision usefulness. Decision usefulness may still be subsidiarily achieved by focusing on accountability. Accountability should be the main conceptual underpinning while decision usefulness is the subsidiary objective. Research implications – As waqf entity embodies the spirit of voluntariness within the realm of Islamic tradition, any effort in developing accounting/reporting standards must be founded upon accountability. Any consideration and decision on the technicalities of accounting on any specific issue must give primacy to accountability over anything else including decision usefulness. Originality/value – This is a dearth in discussing waqf from accounting perspective. This discussion on the objective of providing accounting/reporting information highlights the very initial steps in any standard setting process. Any new accounting standard related to waqf ought to consider this issue in its future undertakings.